Backlight film, method of manufacturing, and display device

CN122958727APending Publication Date: 2026-10-23HKC CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610952899.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,锡基钙钛矿量子点的稳定性不足,限制了其实际应用

Benefits of technology

[0015]本申请提供的背光薄膜的制备方法,通过合成共掺杂有钝化型元素和发光敏化型元素的锡基钙钛矿量子点,利用钝化型元素减少量子点中的缺陷和氧化活性位点,利用发光敏化型元素通过能量传递增强荧光发射,从而从本征层面同步提升量子点的稳定性和发光效率;通过在量子点表面包覆无机壳层,形成物理阻隔屏障,有效隔绝水氧对量子点的侵蚀;通过将核壳结构量子点分散于含有抗氧化剂的聚合物基体中成膜,利用抗氧化剂在聚合物基体内构建化学保护屏障,进一步清除残余的活性氧。上述三重保护机制协同作用,使得制备的背光薄膜兼具高稳定性和高发光效率,满足显示背光的应用要求。包含该背光薄膜的显示装置同样具有上述有益效果,能够实现高色域显示。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958727A_ABST
    Figure CN122958727A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of display, and particularly relates to a backlight film, a preparation method and a display device. The preparation method of the backlight film comprises the following steps: synthesizing tin-based perovskite quantum dots, the tin-based perovskite quantum dots are co-doped with a passivation type element and a luminescence sensitization type element, and the surface of the quantum dots is combined with an organic ligand; coating an inorganic shell layer on at least part of the surface of the quantum dots to obtain core-shell structure quantum dots; and dispersing the core-shell structure quantum dots in a polymer matrix containing an antioxidant, film forming and solidifying. The application can have high stability and high luminescence efficiency, and meet the application requirements of display backlight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of display technology, specifically relating to a backlight film, its preparation method, and a display device. Background Technology

[0002] Lead-free tin-based perovskite quantum dots have attracted attention in the display backlighting field due to their absence of toxic lead. However, the insufficient stability of tin-based perovskite quantum dots limits their practical applications. Summary of the Invention

[0003] The purpose of this application is to provide a backlight film, a preparation method, and a display device that can combine high stability and high luminous efficiency to meet the application requirements of display backlight.

[0004] The first aspect of this application provides a method for preparing a backlight film, comprising the following steps: synthesizing tin-based perovskite quantum dots, wherein the tin-based perovskite quantum dots are co-doped with passivating elements and photosensitive elements, and organic ligands are bound to the surface of the quantum dots; coating at least a portion of the surface of the quantum dots with an inorganic shell layer to obtain core-shell structured quantum dots; dispersing the core-shell structured quantum dots in a polymer matrix containing an antioxidant, and curing them to form a backlight film.

[0005] In one exemplary embodiment of this application, the passivating element is Bi, and the luminescent sensitizing element is Mn; wherein, the step of synthesizing tin-based perovskite quantum dots includes: under a protective atmosphere, dissolving a cesium source, a tin source, a bismuth source, and a manganese source in a solvent as a precursor solution, injecting the solution into a toluene solution containing oleylamine and trioctylphosphine oxide for reaction, cooling, centrifuging and purifying to obtain the tin-based perovskite quantum dots.

[0006] In one exemplary embodiment of this application, the step of injecting the precursor solution into a toluene solution containing oleylamine and trioctylphosphine oxide for reaction includes: heating the toluene solution containing oleylamine and trioctylphosphine oxide to 100~150°C, rapidly injecting the precursor solution, stirring the reaction for 5~20 seconds, and then cooling and quenching.

[0007] In one exemplary embodiment of this application, the step of coating at least a portion of the surface of the quantum dot with an inorganic shell to obtain a core-shell structured quantum dot includes: adding the obtained quantum dot to a zinc source and a sulfur source to react, growing an inorganic shell on at least a portion of the surface of the quantum dot, and centrifuging to purify after the reaction to obtain the core-shell structured quantum dot.

[0008] In one exemplary embodiment of this application, the zinc source is zinc acetate and the sulfur source is thioacetamide. A ZnS shell is grown in situ by a cation exchange reaction at 50-70°C for 2-4 hours, with a shell thickness of 2-4 nm.

[0009] In one exemplary embodiment of this application, the step of dispersing the core-shell quantum dots in a polymer matrix containing an antioxidant includes: dispersing the obtained core-shell quantum dots and the antioxidant together in a polymer solution, casting them onto a substrate, and curing them to obtain the backlight film.

[0010] In one exemplary embodiment of this application, the antioxidant is a compound mixture of α-tocopherol and 2,6-di-tert-butyl-4-methylphenol, wherein the mass fraction of α-tocopherol in the polymer matrix is ​​0.3~0.8 wt%, and the mass fraction of 2,6-di-tert-butyl-4-methylphenol in the polymer matrix is ​​0.1~0.5 wt%; the polymer is polymethyl methacrylate; the curing temperature is 40~60℃, and the thickness of the resulting backlight film is 80~150 μm.

[0011] In one exemplary embodiment of this application, the step of dispersing the core-shell quantum dots in a polymer matrix containing antioxidants further includes: dispersing lead-free perovskite quantum dots with different emission wavelengths than the core-shell quantum dots together with the core-shell quantum dots in the polymer matrix containing antioxidants.

[0012] A second aspect of this application provides a backlight film comprising a polymer matrix and lead-free perovskite quantum dots dispersed in the polymer matrix. The lead-free perovskite quantum dots include at least one core-shell structure quantum dot, which includes tin-based perovskite quantum dots and an inorganic shell coating at least a portion of the surface of the tin-based perovskite quantum dots. The tin-based perovskite quantum dots are co-doped with passivating elements and photosensitive elements, and organic ligands are bound to the surface of the tin-based perovskite quantum dots. An antioxidant is also dispersed in the polymer matrix.

[0013] A third aspect of this application provides a display device, comprising: a display panel and a backlight module; and a backlight film as described above, wherein the backlight film is disposed on the light-emitting side of the backlight module, and the display panel is disposed on the side of the backlight film away from the backlight module.

[0014] The backlight film, preparation method, and display device of this application have at least the following beneficial effects:

[0015] The backlight film preparation method provided in this application involves synthesizing tin-based perovskite quantum dots co-doped with passivating and luminescent elements. The passivating elements reduce defects and oxidation active sites in the quantum dots, while the luminescent elements enhance fluorescence emission through energy transfer, thereby simultaneously improving the stability and luminous efficiency of the quantum dots intrinsically. An inorganic shell is coated onto the surface of the quantum dots to form a physical barrier, effectively isolating them from water and oxygen erosion. Furthermore, the core-shell structured quantum dots are dispersed in a polymer matrix containing antioxidants to form a film, utilizing the antioxidants to construct a chemical protective barrier within the polymer matrix, further eliminating residual active oxygen. This triple protection mechanism works synergistically, resulting in a backlight film with both high stability and high luminous efficiency, meeting the application requirements for display backlights. Display devices incorporating this backlight film also exhibit the aforementioned beneficial effects, enabling high color gamut display.

[0016] Other features and advantages of this application will become apparent from the following detailed description, or may be learned in part from practice of this application.

[0017] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit this application. Attached Figure Description

[0018] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application. It is obvious that the drawings described below are merely some embodiments of this application, and those skilled in the art can obtain other drawings based on these drawings without any inventive effort.

[0019] Figure 1 A schematic diagram of the crystal structure provided in an embodiment of this application is shown.

[0020] Figure 2 A schematic diagram of the core-shell structure formation process provided in an embodiment of this application is shown.

[0021] Figure 3 A schematic diagram of a structure with a ZnS shell provided in an embodiment of this application is shown.

[0022] Figure 4 A schematic diagram of the TEM morphology of the core-shell PQD provided in the embodiment of this application is shown.

[0023] Figure 5 A schematic diagram of the cross-sectional structure of the backlight film provided in an embodiment of this application is shown.

[0024] Figure 6 This illustration shows a schematic diagram of a backlight film with a ZnS shell structure provided in an embodiment of this application.

[0025] Figure 7 A schematic diagram of the preparation method of the backlight film provided in the embodiments of this application is shown.

[0026] Figure 8 A schematic diagram of the preparation process of the backlight film provided in the embodiments of this application is shown.

[0027] Figure 9 A schematic diagram of the structure of the display device provided in an embodiment of this application is shown.

[0028] Explanation of reference numerals in the attached figures: 100. Backlight film; 110. Polymer matrix; 120. Core-shell quantum dot; 121. Tin-based perovskite quantum dot; 122. Inorganic shell layer; 130. Antioxidant; 140. Barrier film; 150. Organic ligand layer; 200. Backlight module; 300. Display panel. Detailed Implementation

[0029] Exemplary embodiments will now be described more fully with reference to the accompanying drawings. However, these exemplary embodiments can be implemented in many forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided to make this application more comprehensive and complete, and to fully convey the concept of the exemplary embodiments to those skilled in the art.

[0030] In this application, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0031] In this application, unless otherwise expressly specified and limited, the terms "assembly," "connection," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.

[0032] Furthermore, the described features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. Numerous specific details are provided in the following description to give a thorough understanding of embodiments of this application. However, those skilled in the art will recognize that the technical solutions of this application can be practiced without one or more of the specific details, or other methods, components, apparatuses, steps, etc., can be employed. In other instances, well-known methods, apparatuses, implementations, or operations are not shown or described in detail to avoid obscuring various aspects of this application.

[0033] Quantum dot backlight enhancement films are key materials for improving the color gamut and energy efficiency of liquid crystal displays. While lead-based perovskite quantum dots exhibit excellent performance, their lead content makes them subject to increasingly stringent environmental regulations, hindering their large-scale application in consumer electronics. Lead-free tin-based perovskite quantum dots 121, due to their tunable bandgap, high luminous efficiency, and excellent optoelectronic properties similar to lead-based materials, are considered the most promising alternative.

[0034] However, tin-based perovskite quantum dots face the core challenge of insufficient intrinsic stability. Divalent tin ions (Sn) 2+ Thermodynamically, it is in a metastable state and is readily oxidized to tetravalent tin ions (Sn) under the influence of oxygen and water molecules. 4+ This oxidation process leads to the generation of numerous tin vacancy defects in the perovskite lattice. These vacancies are not only effective nonradiative recombination centers that directly quench fluorescence emission, but also active sites for further oxidation reactions, triggering a chain degradation reaction. Therefore, the photoluminescence quantum yield (PLQY) of unprotected tin-based perovskite quantum dots in air can drop sharply from an initial 60-70% to below 10% within tens of minutes, far from meeting the lifespan requirements of thousands or even tens of thousands of hours for display backlights.

[0035] To address the aforementioned issues, this application proposes a triple synergistic strategy employing intrinsic doping, surface coating, and substrate protection to systematically improve the stability of tin-based perovskite quantum dots 121 from multiple levels, while simultaneously maintaining high luminous efficiency. The working principle and technical effects are described below from each of the three perspectives.

[0036] See Figure 1 As shown, this application achieves synergistic regulation of intrinsic defects and luminescence performance by co-doping passivating and luminescent elements into tin-based perovskite quantum dots 121.

[0037] The mechanism of passivating elements lies in filling and passivating tin vacancy defects. For example, Bi... 3+ For example, Bi ³+ The ionic radius of Sn 2+ Similar to Bi, it can enter the Sn sites in the perovskite lattice through equivalent or near-equivalent substitution. Because Bi...3+ Bi has a stable trivalent electron configuration and is not prone to valence state changes. 3+ Occupying Sn sites effectively fills existing tin vacancy defects and reduces the formation of new vacancies. Tin vacancies are the main active sites for oxidation reactions; their reduced density directly leads to Sn²⁻ + A significant decrease in oxidation rate. Among them, Bi... 3+ Doping can make Sn 2+ →Sn 4+ The oxidation rate is reduced by approximately 60%, significantly enhancing the intrinsic antioxidant capacity of quantum dots. Meanwhile, Bi... 3+ Doping can also stabilize the perovskite lattice structure, reduce nonradiative recombination caused by lattice distortion, and further improve the fluorescence quantum yield.

[0038] The mechanism of action of luminescent elements lies in enhancing fluorescence emission through energy transfer. Take Mn as an example. 2+ For example, Mn 2+ Partially replaces Sn 2+ After entering the crystal lattice, characteristic dd transition energy levels are introduced near the band edges of the perovskite host. When the perovskite host absorbs excitation light and generates excitons, the exciton energy can be effectively transferred to Mn via energy transfer. 2+ The excited state energy levels of Mn. 2+ When the d electrons transition from the excited state back to the ground state, characteristic orange-red fluorescence emission (approximately 600 nm) is produced. This sensitized energy transfer process has high quantum efficiency, converting exciton energy in the perovskite host that might otherwise be lost through non-radiative pathways into effective radiative recombination, thereby improving the overall fluorescence quantum yield of the quantum dot.

[0039] It should be noted that there is a synergistic gain effect between the passivating element and the photosensitive element. Sole doping of Mn 2+ Although energy transfer channels can be introduced to utilize sensitized energy transfer mechanisms to transfer exciton energies from the perovskite host to Mn. 2+ The dd transition energy level produces orange-red emission at approximately 600 nm, but Mn 2+ Incorporation with Sn² + The difference in ionic radii between the two atoms can cause local distortion of the perovskite lattice. This lattice distortion not only introduces new nonradiative recombination centers but also accelerates the recombination of Sn. 2+ Oxidation of [specific components] may actually reduce the structural stability and luminescence efficiency of quantum dots. Bi [a specific component]... 3+ Co-doping of Bi can effectively compensate for this negative effect. 3+ The ionic radius of Sn² +More closely aligned with and possessing a stable trivalent electron configuration, it can occupy Sn sites through equivalent substitution, filling existing tin vacancies and reducing unsaturated coordination sites in the crystal lattice. This, on the one hand, reduces Sn 2+ The oxidation active site density is reduced, decreasing the oxidation rate by approximately 60%; on the other hand, reducing vacancy defects and compensating for Mn 2+ The introduced lattice distortion significantly reduces the nonradiative recombination probability and extends the exciton lifetime. This extension of exciton lifetime results in the exciton energy shifting towards Mn. 2+ The efficient transfer of Mn² creates the preconditions for this. + The sensitization efficiency is fully utilized.

[0040] The synergistic effect of the two dopants is also reflected in the gain effect at the spectral level. Mn 2+ After doping is introduced, Mn is introduced through the perovskite host. 2+ The sensitization energy transfer of ions involves a partial transfer of exciton energy to Mn. 2+ The dd transition energy level of the quantum dot produces a characteristic orange-red emission secondary peak at approximately 600 nm, which, together with the green main peak of the perovskite matrix at approximately 530 nm, forms a double-peak emission. The emission peak is located at 520–540 nm, with a full width at half maximum (FWHM) of no more than 30 nm. This double-peak emission effectively broadens the spectral coverage of the quantum dot, compensating for the spectral gap of the green quantum dot in the orange-red band, making the spectral distribution of the backlight more continuous and full. In display applications, this spectral broadening helps to improve the color rendering index of the backlight, making the presentation of colors such as red, orange, and skin tone more realistic and natural. By passivating tin vacancy defects, reducing non-radiative recombination channels, and extending exciton lifetime, Bi 3+ To exciton energy to Mn 2+ The efficient transport of Mn ensures the luminescence intensity of the orange-red secondary peak. Without the synergistic effect of dual doping, Mn... 2+ In single-doped systems, due to increased lattice distortion and high defect state density, exciton energy is transferred to Mn. 2+ Previously, a large amount of energy had been lost through non-radiative pathways, resulting in weak or even unobservable intensity of the orange-red subpeak.

[0041] By regulating Bi 3+ and Mn 2+ The doping ratio can be adjusted to further optimize the luminescence performance and stability of quantum dots. The chemical composition of quantum dots can be represented as Cs(Sn) 1-x-y Bi x Mn yThe formula is Br3, where x represents the Bi doping ratio and y represents the Mn doping ratio. For example, the Bi doping ratio x is 0.02–0.05, and the Mn doping ratio y is 0.01–0.03. When x is too low, the passivation effect of tin vacancy defects is insufficient, and the oxidation rate of divalent tin remains high; when x is too high, excessive Bi substitution may introduce new lattice stress, thus reducing the fluorescence quantum yield. When y is too low, the number of Mn luminescent centers is insufficient, resulting in limited energy transfer efficiency and weak orange-red subpeak intensity; when y is too high, the concentration quenching effect between Mn ions intensifies, and exciton energy is lost non-radiatively during migration between Mn ions, also leading to a decrease in fluorescence quantum yield. Within the above selectable range, the photoluminescence quantum yield of quantum dots can reach 75–85%, significantly better than existing lead-free quantum dot schemes, while also possessing the spectral broadening advantage of bimodal emission. The synergistic effect of the two elements achieves a significant improvement in overall performance from both efficiency and spectral dimensions.

[0042] Furthermore, the organic ligands introduced during quantum dot synthesis possess multiple auxiliary protective functions. The amino groups of long-chain alkylamines (such as oleylamine, OAm) can coordinate with metal ions on the quantum dot surface, and the carboxyl groups of long-chain alkyl acids (such as oleic acid, OA) also have coordination capabilities. Together, they form a hydrophobic organic ligand shell, which on the one hand inhibits quantum dot aggregation and maintains good colloidal dispersion; on the other hand, the steric hindrance effect of the hydrophobic long chains partially blocks the diffusion of water and oxygen molecules to the quantum dot surface. The phosphooxy group in trioctylphosphine oxide (TOPO) molecules has strong coordination capabilities, enabling it to form more stable coordination bonds with unsaturated metal sites on the quantum dot surface, forming a double ligand layer structure together with oleylamine. Through the TOPO / OA / OAm double ligand layer strengthening treatment, a denser and hydrophobic protective layer is formed, which not only enhances the protective effect of the ligand layer but also helps to regulate the reactivity of the precursor during the subsequent growth of the inorganic shell 122, promoting uniform shell growth.

[0043] It is worth mentioning that, see Figures 2 to 4 As shown, based on the intrinsic doping control, this application further constructs an inorganic shell 122 on the quantum dot surface for physical barrier. Although the organic ligand layer 150 can delay water and oxygen permeation to some extent, the molecular-level gaps between its organic molecular chain segments are relatively large, and the coordination bonds between the organic ligands and the quantum dot surface may dissociate or be replaced during long-term use, resulting in limited protection durability. Therefore, constructing a dense and stable inorganic shell 122 outside the quantum dot can further improve the stability of the quantum dot.

[0044] This application forms an effective physical barrier by coating the surface of quantum dots with an inorganic shell 122. Inorganic materials have higher density and structural stability than organic materials, and can effectively prevent the diffusion of oxygen and water molecules from the external environment to the quantum dot core.

[0045] In some embodiments, the inorganic shell 122 can be a metal sulfide, such as zinc sulfide (ZnS). Zinc sulfide (ZnS) has a wide bandgap of approximately 3.7 eV and a dense lattice structure, providing excellent physical oxygen barrier properties without affecting the luminescence of quantum dots. After being coated with a ZnS shell, the photoluminescence quantum yield retention rate of quantum dots after being placed in air for 30 days increased from less than 50% to over 80%.

[0046] In some embodiments, a ZnS shell is grown in situ using a cation exchange method. For example, the synthesized quantum dots are dispersed in a solvent, with zinc acetate as a zinc source and thioacetamide as a sulfur source. Under heating conditions, the thioacetamide decomposes to release sulfur. 2- Ions, and Zn 2+ Sn on the surface of quantum dots 2+ Partial cation exchange occurs, leading to in-situ nucleation and growth of zinc sulfide (ZnS) on the quantum dot surface. This in-situ growth method ensures good lattice matching and tight interfacial contact between the shell and the quantum dot core, reducing the density of interfacial defect states and thus maximizing the preservation of the quantum dot's fluorescence quantum yield.

[0047] It is worth noting that if the shell is too thin, the barrier effect is insufficient, and water and oxygen can still penetrate to the quantum dot core; if the shell is too thick, it may introduce lattice mismatch stress, which will reduce the luminescence efficiency and increase light scattering loss. For example, the shell thickness can be 2~4 nm, such as 2 nm, 3 nm or 4 nm, which can achieve the best balance between barrier performance and optical performance. After being placed in air for 30 days, the quantum dot photoluminescence quantum yield retention rate of the uncoated inorganic shell 122 is less than 50%, while the core-shell structure quantum dot 120 coated with zinc sulfide (ZnS) shell can achieve a retention rate of more than 80%.

[0048] In some embodiments, see Figure 5 and Figure 6 As shown, in addition to the physical barrier of the inorganic shell 122, this application also introduces a chemical protective barrier into the polymer matrix 110. While the inorganic shell 122 provides a molecular-level physical barrier, in practical applications, the quantum dots ultimately need to be dispersed within the polymer matrix 110 to form a thin film. Although the polymer matrix 110 macroscopically encapsulates the quantum dots, free volume voids exist between its molecular chains, allowing oxygen and water molecules to slowly diffuse into the vicinity of the quantum dots. Therefore, an antioxidant 130 is introduced into the polymer matrix 110 to construct a chemical protective barrier, forming a third layer of protection against residual permeated water and oxygen.

[0049] This application disperses core-shell structured quantum dots 120 coated with an inorganic shell layer 122 in a polymer matrix 110 containing an antioxidant 130. After film formation, the antioxidant 130 is uniformly distributed within the film. As a reactive oxygen species scavenger, the antioxidant 130 preferentially reacts with free oxygen permeating into the film, consuming the local oxygen concentration and thus forming a chemically protective microenvironment around the quantum dots, further inhibiting Sn. 2+ Oxidation.

[0050] In some embodiments, antioxidant 130 can be used in a compound formulation. α-Tocopherol (vitamin E) is a natural antioxidant 130 with excellent free radical scavenging and reducing properties, capable of efficiently scavenging reactive oxygen species; 2,6-di-tert-butyl-p-cresol (BHT) is a hindered phenol synthesis antioxidant 130 with good thermal stability and long-lasting antioxidant properties. The combined use of these two antioxidants 130, utilizing the high reactivity of vitamin E and the sustained-release properties of BHT, can continuously exert antioxidant protection over a wide temperature range and a long service life. After introducing the compound antioxidant 130, the backlight film 100, under harsh accelerated aging conditions of 85°C and 85% relative humidity for 500 hours, maintained a photoluminescence quantum yield retention rate of over 70%, significantly higher than the backlight film 100 without added antioxidant 130.

[0051] In other embodiments, antioxidant 130 may also be other hindered phenolic antioxidants 130, such as antioxidant 1010, which has a mass fraction of 0.05 to 0.2 wt% in the polymer matrix 110.

[0052] It is worth mentioning that the selection of the polymer matrix 110 also needs to comprehensively consider optical transparency, water and oxygen barrier properties, and processability. Polymethyl methacrylate (PMMA) has excellent light transmittance (visible light transmittance >92%), good film-forming properties, and chemical stability, making it an ideal matrix material for the backlight film 100. PMMA has a glass transition temperature of approximately 105°C, and under normal operating conditions, it is in a glassy state with restricted molecular chain movement, resulting in a lower water and oxygen permeability coefficient than rubber-state polymers.

[0053] In summary, the triple protection mechanism of this application is arranged spatially from the inside out, Bi 3+ / Mn 2+Co-doping and organic ligands passivate defects at the intrinsic level and nanoscale, enhance luminescence, and provide the first hydrophobic barrier; the dense inorganic shell 122 constructs a physical oxygen barrier at the molecular level; and the polymer matrix 110 containing antioxidant 130 constructs a chemical protective barrier at the macroscopic thin film level. These three mechanisms complement and synergistically work together: intrinsic doping reduces the quantum dot's sensitivity to oxidation, the inorganic shell 122 reduces the probability of oxygen molecules reaching the quantum dot surface, and the antioxidant 130 further removes residual oxygen molecules that have penetrated the shell. This enables the tin-based perovskite quantum dot 121 to maintain high luminous efficiency while achieving long-term stability that meets the requirements of display backlight applications.

[0054] See Figure 7 As shown, this application provides a method for preparing a backlight film 100, comprising the following steps: Step S100: Synthesize tin-based perovskite quantum dots 121. The tin-based perovskite quantum dots 121 are co-doped with passivating elements and photosensitive elements, and organic ligands are bound to the surface of the quantum dots.

[0055] For example, the passivating element is Bi, and the luminescent sensitizing element is Mn. The synthesis steps include: under a protective atmosphere, dissolving cesium, tin, bismuth, and manganese sources in a solvent as a precursor solution, injecting it into a toluene solution containing oleylamine and trioctylphosphine oxide for reaction, cooling, and centrifuging purification to obtain the tin-based perovskite quantum dot 121. Further, the obtained quantum dots are subjected to a double-ligand layer strengthening treatment using trioctylphosphine oxide (TOPO), oleic acid (OA), and oleylamine (OAm) to form a denser and hydrophobic protective layer.

[0056] The step of injecting the precursor solution into a toluene solution containing oleylamine and trioctylphosphine oxide for reaction includes: heating the toluene solution containing oleylamine and trioctylphosphine oxide to 100~150°C, rapidly injecting the precursor solution, stirring the reaction for 5~20 seconds, and then cooling and quenching.

[0057] In step S200, an inorganic shell 122 is coated on at least a portion of the surface of the obtained quantum dot to obtain a core-shell structured quantum dot 120.

[0058] The step includes: adding a zinc source and a sulfur source to the dispersion of the quantum dots obtained above to react, growing an inorganic shell layer 122 on at least a portion of the surface of the quantum dots, and centrifuging and purifying after the reaction to obtain core-shell structured quantum dots 120.

[0059] The zinc source is zinc acetate, and the sulfur source is thioacetamide. The ZnS shell is grown in situ through a cation exchange reaction at 50-70°C for 2-4 hours, with a shell thickness of 2-4 nm.

[0060] In step S300, the obtained core-shell structured quantum dots 120 are dispersed in a polymer matrix 110 containing antioxidant 130, and cured to form a backlight film 100.

[0061] Step S300 includes: dispersing the core-shell quantum dots 120 obtained in step S200 together with the antioxidant 130 in a polymer solution, casting them onto a substrate, and curing them to obtain a backlight film 100.

[0062] Antioxidant 130 can be a compound mixture of α-tocopherol and 2,6-di-tert-butyl-p-cresol, wherein the mass fraction of α-tocopherol in polymer matrix 110 is 0.3~0.8 wt%, and the mass fraction of 2,6-di-tert-butyl-p-cresol in polymer matrix 110 is 0.1~0.5 wt%; the polymer is polymethyl methacrylate; the curing temperature is 40~60℃, and the thickness of the resulting backlight film 100 is 80~150 μm, for example, 80μm, 100μm, 120μm, 150μm.

[0063] In some other embodiments, step S300 may further include: dispersing lead-free perovskite quantum dots (not shown in the figure) that have different emission wavelengths from the core-shell quantum dot 120 together with the core-shell quantum dot 120 in a polymer matrix 110 containing antioxidant 130.

[0064] It is worth mentioning that the above-mentioned common dispersion method can be ultrasonic dispersion, with an ultrasonic time of 15 to 60 minutes.

[0065] It should be noted that in the backlight film 100 of this application, the luminescence of the core-shell quantum dot 120 does not originate from the ZnS inorganic shell 122 itself. The ZnS shell is a wide bandgap material, mainly serving as a physical barrier and passivation protection, and does not participate in luminescence itself. The luminescence of the core-shell quantum dot 120 can be achieved by controlling the halogen composition and ratio of the tin-based perovskite core, utilizing the tunable bandgap of the perovskite material, to realize luminescence of different wavelengths, such as green light and red light; alternatively, it can be achieved by doping the quantum dot with luminescent ions, such as co-doping Mn in the tin-based perovskite quantum dots of this application. 2+ By utilizing a sensitized energy transfer mechanism, a characteristic orange-red emission sub-peak is generated at approximately 600 nm, achieving bimodal emission to broaden the spectral coverage. Therefore, by selecting perovskite core materials with different halogen compositions, or by doping different luminescent ions in the core or shell and controlling the doping concentration, core-shell structured quantum dots 120 with different emission colors can be realized, providing a variety of wavelength combinations for the backlight film 100.

[0066] The technical solution of this application will be further described below with reference to specific embodiments.

[0067] Example 1 See Figure 7 and Figure 8 As shown, this embodiment provides a method for preparing a backlight film 100, the specific steps of which are as follows: Step S100: Synthesize tin-based perovskite quantum dots 121.

[0068] In a nitrogen-protected glove box, 0.9 mmol of cesium bromide (CsBr), 0.85 mmol of stannous bromide (SnBr2), 0.03 mmol of bismuth bromide (BiBr3), and 0.02 mmol of manganese bromide (MnBr2) were dissolved in 5 mL of dimethyl sulfoxide (DMSO) and stirred at 80 °C until the solids were completely dissolved, forming a clear and transparent precursor solution. 2 mL of oleylamine (OAm) and 0.5 g of trioctylphosphine oxide (TOPO) were dissolved in 10 mL of toluene as the ligand solvent, and the solution was heated to 120 °C under nitrogen protection while stirring. After the temperature stabilized, the precursor solution was rapidly injected into the ligand solvent. The reaction was stirred for 5–20 seconds after injection, and the reaction vessel was quickly placed in an ice-water bath for cooling and quenching to terminate the reaction. Rapid supersaturation of the precursor concentration through high-temperature instantaneous injection promotes uniform nucleation; rapid cooling yields quantum dots with narrow size distribution.

[0069] The reaction solution was centrifuged at 10,000 rpm for 5 minutes, and the supernatant was discarded. The precipitate consisted of quantum dots with oleylamine and trioctylphosphine ligands bound to their surfaces. See [link to relevant documentation]. Figure 2 As shown. The precipitate was dispersed in toluene to obtain a quantum dot dispersion with a concentration of approximately 10 mg / mL. Further, the obtained quantum dots were subjected to a biligand layer strengthening treatment using trioctylphosphine oxide (TOPO), oleic acid (OA), and oleylamine (OAm) to form a denser and hydrophobic protective layer. The chemical formula of this quantum dot can be represented as Cs(SnO). 96 Bi0. 03 Mn0. 02 The quantum dots, Br3, contain approximately 3 mol% Bi and 2 mol% Mn doping. Fluorescence spectroscopy analysis revealed a biphasic emission pattern: the primary emission peak is located at approximately 530 nm (green light), and the secondary emission peak is located at approximately 600 nm (orange-red light, originating from Mn²⁺). + (dd transition), the total photoluminescence quantum yield is about 82%.

[0070] Step S200, ZnS shell growth.

[0071] See Figure 2As shown, 30 mg of zinc acetate and 10 mg of thioacetamide were added to the above quantum dot toluene dispersion, wherein the amount of zinc acetate added was based on a Zn:Sn molar ratio of 0.2:1. The mixture was heated to 60°C in a water bath and stirred continuously for 4 hours. During this process, thioacetamide gradually decomposed to release S²⁺. - Ions, and Zn² + Sn² on the surface of partially replaced quantum dots + ZnS was nucleated and grown in situ on the surface of quantum dots via cation exchange. After the reaction, the resulting core-shell quantum dots 120 were purified by centrifugation and redispersed in toluene. At this point, the quantum dots had uniform particle size, the ZnS shell thickness was approximately 3 nm, and the lattice fringes were clear, indicating good shell crystallinity. The photoluminescence quantum yield of the quantum dots remained at approximately 82% after the shell coating, indicating that the shell growth process was mild and controllable, and did not cause significant surface etching or defect introduction to the quantum dots.

[0072] Step S300: Backlight film 100 is prepared.

[0073] See Figure 5 and Figure 6 As shown, the core-shell quantum dots 120 and antioxidant 130 were co-dispersed in an ethyl acetate solution of polymethyl methacrylate (PMMA), wherein the mass-to-volume ratio of PMMA to ethyl acetate was 1:4, and the mass fraction of core-shell quantum dots 120 in the polymer matrix 110 was approximately 5 wt%. Antioxidant 130 was a compound formulation of α-tocopherol and 2,6-di-tert-butyl-p-cresol, wherein the mass fraction of α-tocopherol in the polymer matrix 110 was 0.5 wt%, and the mass fraction of 2,6-di-tert-butyl-p-cresol in the polymer matrix 110 was 0.3 wt%. The mixture was ultrasonically dispersed in an ultrasonic cleaner for 30 minutes to ensure uniform dispersion of the quantum dots. The mixture was then cast onto a polyethylene terephthalate (PET) substrate using a doctor blade coating method with a doctor blade spacing of 150 μm, and dried and cured in an oven at 50 °C to obtain a backlight film 100 with a thickness of approximately 100 μm. A double-sided waterproof polyethylene terephthalate barrier film 140 is used to further enhance waterproof and oxygen-proof protection during transportation and storage.

[0074] In this embodiment, a backlight film 100 is prepared using a triple synergistic strategy of Bi / Mn co-doping, ZnS inorganic shell 122 coating, and polymer matrix 110 protection containing antioxidant 130. Among these, Bi... 3+ Doping, by filling tin vacancy defects and reducing oxidation active sites, intrinsically suppresses the oxidation of divalent tin, reducing the oxidation rate by approximately 60%; Mn 2+Doping efficiently transfers the exciton energy of the perovskite host to the dd transition level of Mn through a sensitized energy transfer mechanism, generating an orange-red emission sub-peak at approximately 600 nm. This sub-peak, together with the green main peak of the perovskite host at approximately 530 nm, forms a double-peak emission, increasing the total photoluminescence quantum yield from less than 50% for pure CsSnBr3 quantum dots to 82%. The ZnS inorganic shell 122, with its wide bandgap of approximately 3.7 eV and dense lattice structure, provides effective physical oxygen barrier without affecting quantum dot luminescence, significantly increasing the retention rate of photoluminescence quantum yield in air from less than 50% to over 80%. The α-tocopherol and 2,6-di-tert-butyl-p-cresol compounded in the polymer matrix 110 act as reactive oxygen scavengers, constructing a continuous chemical protective microenvironment within the film and further inhibiting the erosion of quantum dots by residual permeated oxygen. The three mechanisms are arranged sequentially from the inside to the outside in space, and complement and synergize with each other in function, so that the prepared backlight film 100 has both high luminous efficiency and long-term stability.

[0075] Example 2 This embodiment provides a method for preparing a backlight thin film 100 composed of quantum dots with different emission wavelengths. The specific steps are as follows: Following the exact same method as steps S100 and S200 in Example 1, Bi / Mn co-doped ZnS core-shell structure quantum dots 120 were prepared. The emission peak was located at approximately 530 nm, emitting green light, and the photoluminescence quantum yield was approximately 82%.

[0076] Another lead-free double perovskite quantum dot, Cs2AgBiX6, is prepared for red light emission, with its emission peak located at approximately 630 nm. The luminescence of this red quantum dot originates from bandgap transitions within the double perovskite material itself; emission in the red light band can be achieved by controlling its halogen composition and ratio. This red quantum dot has undergone sulfide coating treatment, forming a sulfide protective layer on its surface. The photoluminescence quantum yield is increased to approximately 40% after coating.

[0077] Green core-shell quantum dots 120 and red lead-free perovskite quantum dots were mixed at a mass ratio of 3:1 and dispersed together in a polymethyl methacrylate solution containing α-tocopherol (0.5 wt%) and 2,6-di-tert-butyl-p-cresol (0.3 wt%). Backlight film 100 was prepared by casting and curing process identical to step three of Example S100.

[0078] In this embodiment, a backlight film 100 with a wider spectral coverage was prepared by mixing green Bi / Mn co-doped ZnS core-shell quantum dots 120 with red lead-free double perovskite quantum dots in a specific ratio. The green core-shell quantum dots 120, through a triple protection mechanism of Bi / Mn co-doping, a ZnS inorganic shell 122, and a polymer matrix 110 containing antioxidant 130, maintain high luminous efficiency while exhibiting excellent long-term stability. Their green light emission originates from band-edge recombination of the tin-based perovskite core and Mn... 2+ The backlight emits orange-red light; the red-light lead-free double perovskite quantum dots achieve red light emission by controlling their own halogen composition and ratio. This compensates for the spectral deficiency in the red light band of a single green quantum dot, enabling the backlight to achieve effective coverage in both the green and red light bands, resulting in a more continuous and balanced spectral distribution. The two types of quantum dots are uniformly dispersed in the polymer matrix 110, emitting light independently, reducing spectral crosstalk between different emission centers. The full width at half maximum (FWHM) of the green channel is approximately 28 nm, while the emission peak of the red channel is located at approximately 630 nm. The two are fully separated spectrally, ensuring the color purity of each color channel. Based on the above spectral complementarity effect, the backlight film 100 prepared in this embodiment, after integration into the liquid crystal display backlight module 200, can achieve a wider color gamut coverage than the single green quantum dot solution, with a BT.2020 color gamut coverage exceeding 80%.

[0079] Example 3 See Figure 5 and Figure 6 As shown, this application also provides a backlight film 100, which can be prepared by the preparation method described in any of the above embodiments, or by other methods.

[0080] The backlight film 100 may include a polymer matrix 110 and lead-free perovskite quantum dots dispersed in the polymer matrix 110; the lead-free perovskite quantum dots include at least one core-shell structure quantum dot 120, which includes tin-based perovskite quantum dots 121 and an inorganic shell layer 122 covering at least part of its surface, the tin-based perovskite quantum dots 121 are co-doped with passivating elements and photosensitive elements, and organic ligands are bound to the surface; an antioxidant 130 is also dispersed in the polymer matrix 110.

[0081] It is worth mentioning that the backlight film 100 prepared in Example 1 was integrated into the liquid crystal display backlight module 200 for color gamut testing. Using a blue light-emitting diode as the excitation light source, the backlight film 100 was placed on the light-emitting side of the light guide plate. Part of the blue light excited the quantum dots to produce green and orange-red light, while part of the blue light directly passed through as the blue component of the three primary colors for display. The test results showed that the display module integrating this backlight film 100 achieved 105% NTSC color gamut coverage under the CIE 1931 colorimetric standard.

[0082] In addition, the backlight film 100 prepared in Example 1 was placed in an air environment with a temperature of 25°C and a relative humidity of 50%, and the photoluminescence quantum yield was tested every 24 hours. The results showed that the PLQY retention rate of the film was 82% after 30 days, and the film showed no yellowing, no black spots, and no obvious uneven fluorescence decay.

[0083] The backlight film 100 prepared in Example 1 was placed in a high temperature and high humidity accelerated aging environment of 85°C and 85% relative humidity for 500 hours. The photoluminescence quantum yield of the film was maintained at 71%.

[0084] The mixed-wavelength backlight film 100 prepared in Example 2 was subjected to the same tests. Due to the introduction of red quantum dots, the film has more complete coverage in the red light band, achieving a BT.2020 color gamut coverage of over 80%. The green channel emission peak width is approximately 28 nm, and the red channel emission peak is approximately 630 nm. These two are well separated spectrally, reducing the decrease in color purity caused by spectral crosstalk. The long-term stability test results are comparable to those of Example 1, indicating that the mixed formulation does not negatively affect the overall stability of the film.

[0085] Understandably, through Bi 3+ Doping fills tin vacancy defects, thereby increasing the yield of Sn. 2+ The oxidation rate was reduced by approximately 60%, fundamentally weakening the sensitivity of quantum dots to oxidation, while Bi 3+ The lattice stabilizing effect of Mn cancels out the effect of Mn 2+ The introduced lattice distortion makes high concentrations of Mn 2+ Doping becomes possible; Mn 2+ Doping converts the exciton energy of the perovskite host into Mn through an efficient sensitized energy transfer mechanism. 2+The characteristic dd transition emission of the ZnS quantum dots increased the total photoluminescence quantum yield (PLQY) from less than 50% to over 80% for pure CsSnBr3 quantum dots. The organic ligand layer 150, composed of TOPO and oleylamine, not only ensured the colloidal dispersion stability of the quantum dots but also provided interface regulation for the uniform growth of the ZnS shell. The ZnS inorganic shell 122, with its wide bandgap of approximately 3.7 eV and dense lattice structure, effectively blocked the penetration of external water and oxygen without affecting the luminescence of the quantum dots, significantly increasing the PLQY retention rate of the quantum dots in air from less than 50% to over 80%. The α-tocopherol and BHT compounded in the polymer matrix 110 act as reactive oxygen species scavengers, constructing a continuous chemical protective microenvironment inside the film, further increasing the long-term stability under high temperature and high humidity conditions from less than 100 hours to over 500 hours, while maintaining the PLQY retention rate at over 70%.

[0086] Example 4 See Figure 9 As shown, this application also provides a display device, which may include a display panel 300, a backlight module 200, and the aforementioned backlight film 100 disposed on the light-emitting side of the backlight module 200. The backlight module 200 may include conventional components such as a light source, a light guide plate, a reflective sheet, a diffuser, and a brightness enhancement film. The backlight film 100 is disposed on the light-emitting side of the light guide plate and can replace or be used in conjunction with existing phosphor films. The display panel 300 is disposed on the side of the backlight film 100 away from the backlight module 200. The display panel 300 can be a liquid crystal display panel, a Mini-LED backlit liquid crystal display panel, or any other display device employing a backlight module and quantum dot color conversion film architecture. This display device combines the advantages of wide color gamut, high stability, and environmental friendliness, and is suitable for various terminal display devices such as LCD TVs, desktop monitors, laptops, tablets, automotive displays, and advertising machines, with broad market application prospects.

[0087] In the description of this specification, references to terms such as "some embodiments," "exemplarily," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. The illustrative expressions of the above terms in this specification do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0088] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application. Therefore, any changes or modifications made in accordance with the claims and description of this application should fall within the scope of this patent application.

Claims

1. A method for preparing a backlight film, characterized in that, Includes the following steps: A tin-based perovskite quantum dot was synthesized, wherein the tin-based perovskite quantum dot was co-doped with a passivating element and a photosensitive element, and an organic ligand was bound to the surface of the quantum dot; At least a portion of the surface of the quantum dot is coated with an inorganic shell to obtain a core-shell structured quantum dot. The core-shell structured quantum dots are dispersed in a polymer matrix containing antioxidants and cured to form a backlight film.

2. The preparation method according to claim 1, characterized in that, The passivating element is Bi, and the photosensitive element is Mn; wherein, the steps for synthesizing tin-based perovskite quantum dots include: Under a protective atmosphere, cesium, tin, bismuth and manganese sources were dissolved in a solvent as a precursor solution, which was then injected into a toluene solution containing oleylamine and trioctylphosphine oxide for reaction. After cooling, the solution was purified by centrifugation to obtain the tin-based perovskite quantum dots.

3. The preparation method according to claim 2, characterized in that, The step of injecting the precursor solution into a toluene solution containing oleylamine and trioctylphosphine oxide for reaction includes: The toluene solution containing oleylamine and trioctylphosphine oxide is heated to 100-150°C and then rapidly injected into the precursor solution. After stirring for 5-20 seconds, the mixture is cooled and quenched.

4. The preparation method according to claim 1, characterized in that, The step of coating at least a portion of the surface of the quantum dot with an inorganic shell to obtain a core-shell structured quantum dot includes: The obtained quantum dots were added to a zinc source and a sulfur source to react, and an inorganic shell layer was grown on at least a portion of the surface of the quantum dots. After the reaction was completed, the quantum dots were purified by centrifugation to obtain the core-shell structured quantum dots.

5. The preparation method according to claim 4, characterized in that, The zinc source is zinc acetate, and the sulfur source is thioacetamide. A ZnS shell is grown in situ at 50-70°C for 2-4 hours via a cation exchange reaction, with a shell thickness of 2-4 nm.

6. The preparation method according to claim 1, characterized in that, The step of dispersing the core-shell quantum dots in a polymer matrix containing antioxidants includes: The obtained core-shell structured quantum dots and antioxidants were co-dispersed in a polymer solution, cast onto a substrate, and cured to obtain the backlight film.

7. The preparation method according to claim 6, characterized in that, The antioxidant is a compound mixture of α-tocopherol and 2,6-di-tert-butyl-4-methylphenol, wherein the mass fraction of α-tocopherol in the polymer matrix is ​​0.3~0.8 wt%, and the mass fraction of 2,6-di-tert-butyl-4-methylphenol in the polymer matrix is ​​0.1~0.5 wt%; the polymer is polymethyl methacrylate; the curing temperature is 40~60℃, and the thickness of the resulting backlight film is 80~150 μm.

8. The preparation method according to claim 6 or 7, characterized in that, The step of dispersing the core-shell structured quantum dots in a polymer matrix containing antioxidants further includes: Lead-free perovskite quantum dots with different emission wavelengths than the core-shell quantum dots are dispersed together with the core-shell quantum dots in a polymer matrix containing antioxidants.

9. A backlight film, characterized in that, The backlight film includes a polymer matrix and lead-free perovskite quantum dots dispersed in the polymer matrix. The lead-free perovskite quantum dots include at least one core-shell structure quantum dot, which includes tin-based perovskite quantum dots and an inorganic shell layer covering at least a portion of the surface of the tin-based perovskite quantum dots. The tin-based perovskite quantum dots are co-doped with passivating elements and photosensitive elements, and organic ligands are bound to the surface of the tin-based perovskite quantum dots. Antioxidants are also dispersed in the polymer matrix.

10. A display device, characterized in that, include: Display panel and backlight module; as well as The backlight film as described in claim 9, wherein the backlight film is disposed on the light-emitting side of the backlight module, and the display panel is disposed on the side of the backlight film away from the backlight module.